Parent-child interactions and adolescent misbehaviour - Jamaluddin, Zakiyah (Jabatan Antropologi dan Sosiologi, Fakulti Sastera dan Sains Sosial, Universiti Malaya, 2011)
This paper addresses issues of adolescents' misbehavior in one of the low cost flat housing areas in Kuala Lumpur. The objective of the study was to examine parent-child interactions and its effect on adolescent' misbehavior. A total of 19 participants including 11 adolescent, three mother, two UMNO branch leaders an MCA women leader a former Surau (prayer hall) Chairman and the former internet cafe staff were chosen by purposive and snowball techniques. This study found that parent-child interactions for those participants was associated to adolescent misbehavior. Adolescent misbehavior appeared to be due to a lack of parental support and control behavior, economic pressure and adolescent rebellion and factors related to adolescents school.